2005
DOI: 10.1021/es0485715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Catalyst Concentration on Photocatalytic Oxidation of Aqueous Ammonia and Nitrite in Titanium Dioxide Suspensions

Abstract: Batch experiments were conducted to study the effects of titanium dioxide (TiO2) concentration and pH on the initial rates of photocatalytic oxidation of aqueous ammonium/ ammonia (NH4+/NH3) and nitrite (NO2-) in UV-illuminated TiO2 suspensions. While no simple kinetic model could fit the data at lower TiO2 concentrations, at TiO2 concentrations > or = 1 g/L, the experimental data were consistent with a model assuming consecutive first-order transformation of NH4+/NH3 to NO2- and NO2- to nitrate (NO3-). For Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
92
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 34 publications
14
92
0
1
Order By: Relevance
“…Several studies have investigated wastewater purification by the photocatalytic oxidation of aqueous ammonia using TiO 2 and/or PtTiO 2 [9][10][11][12][13][14]. Some of these studies reported the effect of pH [9,10], whereas others focused on the effects of Pt loading on the TiO 2 [13] or the presence of inorganic anions [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated wastewater purification by the photocatalytic oxidation of aqueous ammonia using TiO 2 and/or PtTiO 2 [9][10][11][12][13][14]. Some of these studies reported the effect of pH [9,10], whereas others focused on the effects of Pt loading on the TiO 2 [13] or the presence of inorganic anions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies reported the effect of pH [9,10], whereas others focused on the effects of Pt loading on the TiO 2 [13] or the presence of inorganic anions [14]. In these studies, the initial concentrations of ammonia in the reaction solution were on the order of ppm (∼10 −4 M), and relatively long reaction times were required for oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of ammonia in wastewater effluents deplete dissolved oxygen, reduce chlorine disinfection efficiency, and exhibit acute toxicity to aquatic life. There are several methods for ammonia removal from water and wastewater, including biological process (Kalyuzhnyi et al, 2006), ammonia stripping (Bonmati and Flotats, 2003), ion exchange (Lin and Wu, 1996), breakpoint chlorination (Thomas et al, 1972), photocatalysis (Zhu et al, 2005) and electrochemical process (Chiang et al, 1995;Kim et al, 2006;Wang et al, 2006). Electrochemical method for the advanced treatment of ammonia in the wastewater has attracted a great deal of attention because of its advantages such as a minimal generation of secondary waste, easy operation, remote control, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Merujuk pada penelitian yang dilakukan oleh Putra (2015), Mohammadi, Sharifnia, dan Shavisi (2016), (Zendehzaban, Sharifnia, dan Hosseini 2013), dan (Zhu et al 2004), degradasi amonia mengikuti model kinetika Langmuir-Hinshelwood, sehingga Model Langmuir-Hinshelwood digunakan untuk mengetahui kinetika reaksi dari degradasi amonia menggunakan fotokatalisis pada penelitian ini.…”
Section: Pengaruh Konsentrasi Limbah Amoniaunclassified